Leyes que rigen la libertad de expresión del historiador: una visión comparativa en el mundo contemporáneo (Debates) - Baets, Antoon De (2019)
This article provides a comparative approach to laws that interfere directly with the free expression of historians, that is, with respect to what they say and write. This body of international law is gathered together into four groups: memory laws, blasphemy laws, hate speech laws, and laws against genocide denial. To examine each group, the article provides a definition and identifies how standards overlap. Finally, the most relevant debates are summarized with respect to their consequences for practicing history.